PERBANDINGAN EFISIENSI INHIBISI KOROSI BAJA OLEH EKSTRAK DAUN TEH DENGAN CAMPURAN EKSTRAK DAUN TEH DAN KALSIUM GLUKONAT - ., Yerimadesi; Mon, Irma; Elsa Mona, Dewi (Sainstek, 2010)
The inhibition efficiency of steel corrosion by tea leaf extract and mixture of tea leaf extract and calcium gluconate was studied by using weight loss techniques. The steel sample has the code of ASSAB 760 (AISI 1148, 0.5%) and the tea leaf sample used is the old tea leaf. The inhibition efficiency by mixture of tea leaf extract and calcium gluconate is higher than the inhibition efficiency by tea leaf extract. Key words: inhibition efficiency of steel corrosion, tea leaf extract, tea leaf extract/calcium gluconate blends, inhibitor.